2005
DOI: 10.1038/sj.bjp.0706281
|View full text |Cite
|
Sign up to set email alerts
|

Differing mechanisms of leukocyte recruitment and sensitivity to conditioning by shear stress for endothelial cells treated with tumour necrosis factor‐α or interleukin‐1β

Abstract: 1 The cytokines tumour necrosis factor-a (TNFa) and interleukin-1b (IL-1B) induce endothelial cells to recruit leukocytes. However, the exact adhesion and activation mechanisms induced by each cytokine, and their relative sensitivities to modulation by endothelial exposure to shear stress remain unclear.2 We cultured human umbilical vein endothelial cells (HUVEC) in glass capillaries at various shear stresses, with TNFa or IL-1B added for the last 4 h. Subsequently, human neutrophils were perfused over the HUV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
2
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 46 publications
4
39
2
2
Order By: Relevance
“…Antibodies against CXC chemokine receptor 1 (CXCR1) or CXCR2 (Clones 501 and 19, Biosource International Inc., Camarillo, CA) were used at 2 μg/ml, according to the manufacturer's recommendation. In recent, flow-based studies, we have found these antibodies to inhibit neutrophil migration through TNF-treated HUVEC and also to increase the percentage of the captured cells undergoing rolling [25,26]. This indicates that they inhibit migration through blockade of activation rather than by mimicking the natural CXC chemokine agonists.…”
Section: Treatments With Antibodies and Inhibitory Agentsmentioning
confidence: 99%
“…Antibodies against CXC chemokine receptor 1 (CXCR1) or CXCR2 (Clones 501 and 19, Biosource International Inc., Camarillo, CA) were used at 2 μg/ml, according to the manufacturer's recommendation. In recent, flow-based studies, we have found these antibodies to inhibit neutrophil migration through TNF-treated HUVEC and also to increase the percentage of the captured cells undergoing rolling [25,26]. This indicates that they inhibit migration through blockade of activation rather than by mimicking the natural CXC chemokine agonists.…”
Section: Treatments With Antibodies and Inhibitory Agentsmentioning
confidence: 99%
“…In response to TNF-␣, neutrophil recruitment (adherence and transmigration) was reduced in a shear-dependent manner, with a concomitant reduction in cytokine-induced expression of E-selectin, IL-8, and Gro-␣, whereas no such difference was observed for IL-1␤. 62 The mechanism underlying these observations remains unidentified, but the emergence of flowinduced transcription factors such as Kruppel-like factor 2 (KLF)2 might provide an explanation (see below for detailed discussion on KLF2).…”
Section: Regional Recruitmentmentioning
confidence: 99%
“…20 However, cultured EC, which had been subjected to PECAM-1 small interfering RNA knock down, did not align in response to laminar high shear, but remained polygonal, 20 a phenotype found in areas of arteries prone to atherogenesis. Generally, laminar shear stress suppresses the inflammatory responses of EC, 21,22 and we have recently shown that this protective effect also requires expression of PECAM-1. 23 Thus, taken together, these results indicate that PECAM-1 may play roles in the proinflammatory response believed to promote atherogenesis in regions of disturbed flow and in the protective effects of laminar, high shear stress.…”
mentioning
confidence: 99%